The effect of green bean juice and oxytocin massage on breast milk production in breastfeeding mothers - Ayuningtyas, Ika Fitria; Hidiyaningtyas, Lutfi; Ekawati (MEDIA ILMU KESEHATAN, 2025)
Background: Optimal breast milk production is crucial for a baby's health. Common problems include low milk supply, blocked milk ducts, and anatomical breast issues. These factors include poor breastfeeding technique, stress and fatigue, poor nutrition, and delayed milk production.Objective: To determine the effect of giving green bean juice and oxytocin massage on breast milk production.Methods: The study employed a pretest-posttest design with a control group, divided into two groups: one receiving green bean juice and the other receiving oxytocin massage.Results: The statistical test T-test sig value 0.512 (>0.05), there is no significant difference between giving green bean juice and oxytocin massage on breast milk production. The green bean juice group has a value (3273) higher than the oxytocin massage group (3180), although there is no significant difference, but the giving of green bean juice has a slightly greater effect on breast milk production.Conclusion: Giving green bean juice has a slightly greater effect on breast milk production than giving oxytocin massage. Giving green bean juice and oxytocin massage to postpartum mothers simultaneously increased breast milk production